Gut microbiota influence acute pancreatitis through inflammatory proteins: a Mendelian randomization analysis - Huang, Peiyao; Liu, Qiang; Zhang, Tianlong; Yang, Jianfeng (Frontiers in Cellular and Infection Microbiology, 2024)
Background/Aim: We employed Mendelian Randomization (MR) analysis to investigate the causal relationship between the gut microbiota, acute pancreatitis, and potential inflammatory proteins.Methods: The data for gut microbiota, acute pancreatitis, and inflammatory proteins are sourced from public databases. We conducted a bidirectional MR analysis to explore the causal relationship between gut microbiota and acute pancreatitis, and employed a two-step MR analysis to identify potential mediating inflammatory proteins. IVW is the primary analysis method, heterogeneity, pleiotropy, and sensitivity analyses were also conducted simultaneously.Results: We identified five bacterial genera associated with the risk of acute pancreatitis, namely genus.Coprococcus3, genus.Eubacterium fissicatena group, genus.Erysipelotrichaceae UCG-003, genus.Fusicatenibacter, and genus.Ruminiclostridium6. Additionally, we have discovered three inflammatory proteins that are also associated with the occurrence of acute pancreatitis, namely interleukin-15 receptor subunit alpha (IL-15RA), monocyte chemoattractant protein-4 (CCL13), and tumor necrosis factor receptor superfamily member 9 (TNFRSF9). Following a two-step MR analysis, we ultimately identified IL-15RA as a potential intermediate factor, with a mediated effect of 0.018 (95% CI: 0.005 -0.032).Conclusions: Our results support the idea that genus.Coprococcus3 promotes the occurrence of acute pancreatitis through IL-15RA. Furthermore, there is a potential causal relationship between the gut microbiota, inflammatory proteins, and acute pancreatitis. These findings provide new insights for subsequent acute pancreatitis prevention.